Chez Burn / Muhammad Bukhairi Dulgamin ... [et al.] - Dulgamin, Muhammad Bukhairi; Azli, Ahmad Zuhair; Bustamam, Nurman Harith Al Zikry; Mohamed Shamshudin, Mohamed Rafie; Wahap, Mohd Ezaidi (2021)
This business is a jointly undertaken business partnership. The business will be run by five people who hold positions as General Manager, Administration Manager, Marketing Manager, Operations Manager and Financial Manager. Chez Burn Food Truck is located next to USTAD Restaurant at No. A AG/50, Jalan Plumbum A A7/AA, Blok E, Pusat Komersial D.E, Seksyen 7, 40000 Shah Alam, Selangor. Our company began operations in June 2021. Our business concept is based on cheese. We will provide cheese -based food and the most important is the cuisine with cheese that is baked along with the food, this matter attracts the attention of customers because nowadays the community is very fond of cheese -based cuisine. Therefore, we are happy to provide very much cheese -based food to satisfy the craving of the community. Our target market is workers, students and teenagers who are around the area. From our observation, in the area there are very many people which makes the place the most strategic place for us to conduct our business. In addition, USTAD Restaurant is also a restaurant that has many customers, especially in the afternoon, evening and at night. The food we provide is edible by everyone no matter from adults to children, and our food is also guaranteed halal because we only use halal-based ingredients. Nevertheless, our food and products can be eaten by everyone regardless of whether they are Indians, Chinese, Malays, and others. As a new company, we have heavy competition because there are more companies that are more experienced than us in the food truck business like Hungry Thug and Mad Miles. However, in business, nothing is perfect, there are weaknesses and advantages. Therefore, we will analyse every weakness to make our company better. Furthermore, we provide social sites such as Facebook and Instagram that make our food and products easy to identify and convenient to be obtained.